The efficacy and safety of different systemic combination therapies on advanced hepatocellular carcinoma: a systematic review and meta-analysis - Li, Ping; Hu, Ming; Liu, Mei; Ren, Xiangyu; Liu, Donghong; Liu, Jiluo; Yin, Jianhua; Tan, Xiaojie; Cao, Guangwen (Frontiers in Oncology, 2023)
Background & Aims: Systemic combinations have recently brought significant therapeutic benefits for advanced hepatocellular carcinoma (aHCC). To design the most effective combination regimens, a systematic review (PROSPERO ID: CRD42022321949) was conducted to evaluate the efficacy and safety of systemic combinations on aHCC. Methods: We retrieved all the studies from PubMed, Embase, CENTRAL, and CNKI using the MeSH terms until Dec 21, 2022. The effect indicators (hazard ratio [HR], relative risk [RR], median were pooled by the fixed or random effect model. The subgroup analysis was conducted according to types and specific therapies. Results: In total, 88 eligible studies were selected from 9748 potential records. Each kind of combined treatments (chemotherapy plus chemotherapy, targeted plus ICI therapy, targeted plus chemotherapy, targeted plus targeted therapy) had a better objective response rate (ORR) in patients with aHCC, compared to the monotherapy mostly with sorafenib (RR: 1.57 [1.44-1.71]; I2=30%). Of those, targeted plus ICI therapy showed better therapeutic efficiency in overall survival (median: 15.02 [12.67-17.38]), progression-free survival (median: 7.08 [6.42-7.74]), and ORR (RR: 1.81 [1.55-2.13]), compared to the monotherapy. Specifically, Atezo plus Beva showed all those benefits. Our pooled result showed all the combinations had increased ≥3 Grade treatment related adverse events (TrAEs), with a RR of 1.25 [95% CI: 1.15-1.36], compared to the monotherapy. Conclusion: The systemic combinations especially targeted plus ICI therapy, including Atezo plus Beva significantly improve clinical outcomes, but increase side effects in patients with aHCC. Future trials should concentrate on improvement in therapeutic efficiency and reduction of toxicity of targeted plus ICI therapy.